Does Social Property Exist? - Trazegnies Granda, Fernando de (1973)
This article aims to elucidate the term "social property" as articulated in the Draft Decree Act of Social Property, issued on August 31, 1973, by the Revolutionary Government of the Armed Forces of Peru. Through a dual legal and social science lens, an examination is conducted to discern the concept and fundamental characteristics of property within the legal framework, juxtaposed with the definition of social property outlined in the draft legislation. The analysis reveals that while property is traditionally defined within liberal categories, the conception of social property as delineated in the bill deviates from classical liberal principles, leading to the conclusion that, in a stric sense, it would not be property.